The effect of crude protein withdrawal and the use of oscillated crude protein concentration on feedlot performance, carcass merit, and ammonia emissions from the pen surface of feedlot steers - Westover, Elin C., author; Wagner, John J., advisor; Engle, Terry E., advisor; Ham, Jay M., committee member (Colorado State University. Libraries, 2011)
Six hundred crossbred steers (BW, 329.7 ± 7.58 kg) were used to investigate the effect of CP withdrawal and the use of oscillating CP concentrations on feedlot performance, digestibility, carcass merit, and ammonia emissions from the pen surface of yearling steers. Steers were randomly assigned to one of the following treatments: HCP [Control, 13.5% CP, 3.5% CP equivalents (CPE)]); OCP (11.62% CP, 1.5% CPE fed Wednesday, Thursday, and Sunday and the HCP diet fed Monday, Tuesday, Friday, and Saturday); EICP (12.56% CP from d28 to slaughter, 2.53% CPE); ELCP (11.62% CP from d28 to slaughter, 1.55% CPE); LICP (HCP throughout with the ICP diet fed the last 27d); and LLCP (HCP throughout with the LCP diet fed the last 27d). Urea was used to modify dietary CP concentrations. Steers were housed in 9-steer pens (n=48) or 7-steer mass balance pens (n=24). Steers were weighed and ultrasound images and fecal grab samples were taken 3 or 4 times (depending upon replicate) throughout the trial. Feed samples, fecal grab samples, and mass balance pen surface samples were analyzed for DM, AIA, N, and P. Soil samples were obtained from the mass balance pens for treatments HCP, OCP, and ELCP and tested for total ammonia volatilization. Steers were harvested on d 149 or d 175 and camera carcass data was collected. Although initial BW differences between treatments were not significant (P > 0.18), initial BW was a significant (P < 0.10) source of variation describing interim and final BW and was therefore included in the data analysis as a covariate. There were no treatment differences for BW (P > 0.23) throughout the study. Average daily gain for each time period or for the entire study was not affected by treatment (P > 0.26). There was a difference (P < 0.05) in DMI between treatments from d 106 to slaughter (HCP > ELCP, LLCP, and LICP), and overall DMI tended (P < 0.11) to be affected by treatment (HCP > ELCP and LLCP). Treatment differences for G: F and net energy recovery were not significant (P > 0.30). There were no significant (P > 0.21) effects of dietary treatment on carcass merit. Treatment differences for DM digestibility calculated from DMI and fecal output as estimated by AIA, were not significant (P > 0.37) and averaged 85.7, 83.6, 84.2, and 83.0% for the HCP, OCP, EICP, and ELCP diets respectively. Treatment differences for CP digestibility, calculated from N intake and fecal N, were significant (P < 0.001) and averaged 83.3, 76.6, 78.8, and 74.3% for the HCP, OCP, EICP, and ELCP diets respectively (HCP > OCP, EICP, and ELCP). Nitrogen intake was significantly (P < 0.0001) affected by treatment and averaged 183, 172, 167, and 155 g per head daily for the HCP, OCP, EICP, and ELCP treatments respectively. Differences between treatments for amount of fecal N (P > 0.18) and calculated amount of retained N (P > 0.42) were not significant. Urinary N, calculated as N intake minus fecal and retained N, excretion was reduced (P < 0.0001) as N intake decreased with treatment averaging 128, 111, 108, and 94 g per steer daily for the HCP, OCP, EICP, and ELCP treatments, respectively. Retained N as a percentage of N intake increased (P < 0.0001) and calculated urinary N excretion decreased (P < 0.001) with decreasing N intake associated with treatment averaged 12.6, 13.6, 14.1, and 15.0% and 69.8, 64.6, 64.6, and 60.7% of N intake for the HCP, OCP, EICP, and ELCP treatments respectively. Cattle on the ELCP diet had significantly lower N loss than the HCP treatment (P < 0.02) and the OCP treatment (P < 0.10) for sampling from d 45 and d 92. Similar results were observed from samples taken on d 148; however there were no significant differences. Ammonia flux reduction of ELCP diet compared to HCP diet decrease from 40% to 21% with increasing days on feed. The average ammonia flux over the feed period for all treatments was 147.3 g/m2/d. There were no treatment differences (P > 0.36) for N, P, or N: P ratio found in samples from manure cleaned from the pen surface at the end of the study. Nitrogen to P ratios ranged from 2.13 to 2.23 and was lower than the fecal grab sample N: P ratio. These results indicate that ADG and carcass merit were similar for steers fed OCP and CP withdrawal diets as compared with the HCP control. Although DMI declined during the later stages of the finishing period, feed efficiency was not impacted by OCP or CP withdrawal diets. Reduced CP intake whether it was through the OCP or CP withdrawal diets was associated with less urinary N excretion and lower ammonia emissions from the pen surface.